Personnel management of construction companies - Saloid, N.V. (Ways to Improve Construction Efficiency, 2021)
This article discusses the features of construction as an industry, identifies factors that affect the process of personnel management of construction companies in modern conditions. Differences in the organization of the construction process from the production process in other industries are identified, taking into account the specifics of innovative development of the construction industry and staffing requirements, taking into account trends in the industry. Trends in the labor market in construction are shown, foreign and domestic experience in the development of supply and demand in the labor market is analyzed, taking into account the requirements for education, age, level of training. It is concluded that the personnel management system of a modern construction company should take into account the peculiarities of the construction industry, its current problems and global trends in approaches to personnel management. It is determined that in modern conditions the personnel management system of the enterprise takes into account both material and moral motivation, the main components of the motivational process are analyzed, the influence of certain types of motivation on different groups of personnel. The article defines that currently the main component of personnel management of the enterprise is the creation of conditions for the expansion of knowledge, training, skills development and continuous development of employees. The growing role of knowledge in society, the development of science-intensive, intelligent technologies requires flexible and adaptive use of human resources of the construction company, increasing the creative and organizational activity of employees, the formation of a humanized organizational culture. In the conditions of market relations, introduction of new technologies into production, adequate methods of personnel development management, which are based on progressive approaches to the expansion of its competencies, acquire special significance. In view of this, in modern production there are problems of modernization of classical personnel management systems and the introduction of new management models focused on the continuous development of intellectual, cultural and creative potential of construction workers. From an economic point of view, the simultaneous influence of a number of factors on the development of personnel management creates certain contradictions. On the one hand, it is - reducing staff turnover, increasing the level of competencies, ensuring the growth of profits, on the other - significant costs for improving methods of personnel development management. This contradiction shapes the purpose and content of personnel development management tasks and approaches to solving them.